PENGARUH VARIASI WARNA PLAT KOLEKTOR SURYA TERHADAP KINERJA PEMANAS AIR TENAGA SURYA - Harizalni SE; Aris Zainul Muttaqin; Santoso Mulyadi (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2014)
Solar water heater is a device that heats water using solar collectors as a heat absorber of solar radiation that is transmitted to the pipe containing water . In this research, comparative performance testing of solar water heating to solar collector plate color variations . Variations of color used is black ( black ) no. ( 39 ) with the brand of quick drying formula zuper spray acrylic spray paint , red ( red signal ) no. ( 23 ) with rj LONDON acrylic paint brand epoxy spray paint , and blue ( blue fluorescent ) no. ( 1004) with rj LONDON acrylic paint brand spray paint epoxy Data collection was performed by taking data every 30 minutes for 3 hours are 9:00 to 12:00 pm at the clock and the test performed 3 times on different days . Data taken from the study include inlet and outlet water temperature collectors , and the temperature of the water in the tank , which is then carried out data processing to determine the flow rate , the density of water , the water temperature difference in and out collector ( ÄT ) , the performance of solar water heaters ( q ) , and processing the data graphically . The results of the study of each color plate solar collector plate showed that the color black has the highest absorption compared with red and blue , because the color black has emissivity close to 1 ( objects that are almost black) is a transmitter as well as a good heat absorber. Kata kunci: Kolektor, emisivitas, warna plat, air